Benthic marine algae of the coast of Campeche, Mexico - Mateo-Cid, Luz Elena; Mendoza-González, A. Catalina; Ávila-Ortiz, Alejandrina G.; Díaz Martínez, Sergio (Instituto de Ecología, A.C., 2013)
We present results of the study on benthic marine algae in eight localities from the coast of Campeche, Mexico. The results indicate the presence of 211 taxa of marine algae with Rhodophyta having the greatest diversity with 102 taxa, followed by Chlorophyta with 66 taxa, six varieties and four forms, Heterokontophyta with 19 species and finally Cyanobacteria with 14. The floristic list is accompanied by data on presence, seasonality, reproduction, tidal level and references. Of the 211 taxa, 30 are new records for Campeche, with Centroceras micracanthum and Streblonema invisibile being new records for the occidental coast of the Atlantic of Mexico. Species diversity was compared between the rainy and the dry seasons during 2003, 2004, 2006 and 2007. The algal flora of the coast of Campeche is tropical and the greatest diversity was found during the dry season.